Pengaruh Penggunaan Model Problem Based Learning terhadap Hasil Belajar Perkalian Dasar Siswa Kelas III SD - I Kadek Todi Darma Putra Permana; I Made Agus Setiawan; I Gede Agus Subawa; I Made Sujana Adnyana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Problem Based Learning model on improving the basic multiplication learning outcomes of third-grade elementary school students. The research employed a quantitative approach using a pre-experimental design with a one-group pretest-posttest method. The subjects of this study were 28 third-grade students at an elementary school. Data were collected through tests, observations, and documentation. The results showed that the implementation of the Problem Based Learning model significantly improved students’ learning outcomes in basic multiplication material. Students became more active, enthusiastic, and better able to understand multiplication concepts through problem-solving activities related to daily life situations. In addition, the learning process encouraged students to think critically, collaborate with peers, and participate actively during classroom activities. Therefore, the Problem Based Learning model can be used as an effective alternative learning model to improve mathematics learning outcomes, especially in basic multiplication material for third-grade elementary school students